Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the given problem, we need to find the value of the expression \(\frac{(x + y)^2}{(x - y)^2}\) given that \(3x = 4y\).
Step 1: Express \(y\) in terms of \(x\)
Starting from the equation \(3x = 4y\):
[tex]\[\begin{aligned} 3x &= 4y \\ y &= \frac{3}{4}x \end{aligned}\][/tex]
Step 2: Express \(x + y\) and \(x - y\) in terms of \(x\)
Now substitute \(y\) back into the expressions \(x + y\) and \(x - y\):
[tex]\[ x + y = x + \left(\frac{3}{4}x\right) = x + \frac{3}{4}x = \frac{4}{4}x + \frac{3}{4}x = \frac{7}{4}x \][/tex]
[tex]\[ x - y = x - \left(\frac{3}{4}x\right) = x - \frac{3}{4}x = \frac{4}{4}x - \frac{3}{4}x = \frac{1}{4}x \][/tex]
Step 3: Find the squares of these expressions
[tex]\[ (x + y)^2 = \left(\frac{7}{4}x\right)^2 = \left(\frac{7x}{4}\right)^2 = \frac{49x^2}{16} \][/tex]
[tex]\[ (x - y)^2 = \left(\frac{1}{4}x\right)^2 = \left(\frac{x}{4}\right)^2 = \frac{x^2}{16} \][/tex]
Step 4: Determine the ratio of these squares
[tex]\[ \frac{(x + y)^2}{(x - y)^2} = \frac{\frac{49x^2}{16}}{\frac{x^2}{16}} = \frac{49x^2}{16} \times \frac{16}{x^2} \][/tex]
Since \( \frac{49x^2}{16} \times \frac{16}{x^2} = 49 \):
[tex]\[ \frac{(x + y)^2}{(x - y)^2} = 49 \][/tex]
Therefore, the value of [tex]\(\frac{(x + y)^2}{(x - y)^2}\)[/tex] is [tex]\(\boxed{49}\)[/tex].
Step 1: Express \(y\) in terms of \(x\)
Starting from the equation \(3x = 4y\):
[tex]\[\begin{aligned} 3x &= 4y \\ y &= \frac{3}{4}x \end{aligned}\][/tex]
Step 2: Express \(x + y\) and \(x - y\) in terms of \(x\)
Now substitute \(y\) back into the expressions \(x + y\) and \(x - y\):
[tex]\[ x + y = x + \left(\frac{3}{4}x\right) = x + \frac{3}{4}x = \frac{4}{4}x + \frac{3}{4}x = \frac{7}{4}x \][/tex]
[tex]\[ x - y = x - \left(\frac{3}{4}x\right) = x - \frac{3}{4}x = \frac{4}{4}x - \frac{3}{4}x = \frac{1}{4}x \][/tex]
Step 3: Find the squares of these expressions
[tex]\[ (x + y)^2 = \left(\frac{7}{4}x\right)^2 = \left(\frac{7x}{4}\right)^2 = \frac{49x^2}{16} \][/tex]
[tex]\[ (x - y)^2 = \left(\frac{1}{4}x\right)^2 = \left(\frac{x}{4}\right)^2 = \frac{x^2}{16} \][/tex]
Step 4: Determine the ratio of these squares
[tex]\[ \frac{(x + y)^2}{(x - y)^2} = \frac{\frac{49x^2}{16}}{\frac{x^2}{16}} = \frac{49x^2}{16} \times \frac{16}{x^2} \][/tex]
Since \( \frac{49x^2}{16} \times \frac{16}{x^2} = 49 \):
[tex]\[ \frac{(x + y)^2}{(x - y)^2} = 49 \][/tex]
Therefore, the value of [tex]\(\frac{(x + y)^2}{(x - y)^2}\)[/tex] is [tex]\(\boxed{49}\)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.